Rating engineering characteristics in open design using a probabilistic language method based on fuzzy QFD. (September 2019) - Li, Shipei; Tang, Dunbing; Wang, Qi
Highlights: A method is proposed to identify the relation intensity between CR and EC. A calculated model is suggested to normalize the relationships between CRs and ECs. A utility-based evaluation approach is proposed to rate ECs based on the fuzzy QFD. The proposed approach can be used to rate ECs by the CRs expressed freely in OD. Abstract: Identifying the importance weights of engineering characteristics (ECs) is essential for allocating resources in product design. Quality function deployment (QFD) is widely used for rating ECs to satisfy consumer requirements (CRs). In existing approaches, ECs were rated by designers from CRs. With the development of the Internet, open design (OD) is exerting an increasing important effect, and consumers can freely express their requirements for the product. However, in OD environment there will be a large number of CRs expressed using the free text without the guide of purposive questions and the CRs are characterized by uncertainty and diversity of meaning, which makes it hard to rate ECs using the previous methods. To overcome the problem, this paper proposes an extended probabilistic language method based on fuzzy QFD to determine the importance weights of ECs according to the context of CRs in OD. The method focuses on considering the impact of the words in CRs to identify the relationships between CRs and ECs in OD. Meanwhile, a calculated model and a utility-based evaluation approach are suggested to rate ECs based on the fuzzy QFD. An example of the smartphone is given to illustrate the applicability of the proposed method.